Asymptomatic Gastric Giant Polyp in a Boy with Peutz-Jeghers Syndrome Presented with Multiple Café Au Lait Traits - Christos Plataras; Efstratios Christianakis; Florentia Fostira; George Bourikis; Maria Chorti; Dimitrios Bourikas; Nikolaos Fotopoulos; Konstantinos Damalas; Khalil Eirekat (Case Reports in Surgery)
We describe an asymptomatic case of PJS in a six-year-old boy with café au lait spots in several parts of his body, a large gastroduodenal polyp, two polyps near the ampulla of Vater, and another in the jejunum. This patient shows some unique aspects of PJS. No other such large gastric polyp in a Peutz-Jeghers child is reported in the literature. The large size of the gastric polyp with lack of symptoms is unusual and poses a unique challenge in terms of management and surgical resection.